Impact of Corporate Social Responsibility on Value Creation: The Mediating Role of Innovative Performance - Huma Nausheen; Yassir Mahmood; Muhammad Imran; Zubair Ahmad (Journal of Management Practices, Humanities and Social Sciences, 2022)
Corporate Social Responsibility (CSR) and innovation performance are vital constituents of value creation. In this regard, the present study investigated the mediating role of innovation performance between corporate social responsibility and value creation in citrus firms of the Sargodha region. This quantitative research collected data through a survey questionnaire using a purposive sampling technique from 350 respondents. The data analysis tool deployed was SPSS. The results depicted that CSR has significant positive effects on innovation performance. Also, innovation on performance has a strong association with value creation. The role of innovation performance as a mediator between CSR and value creation was also affirmed through Hayes Process model 4. Discussion on these results, along with recommendations for practitioners and policymakers, are also included at the last of the research. This study will open new avenue for scholars and as well for practitioners in different sectors.